Efforts to Improve Student Learning Outcomes in Islamic Education Learning Using Audio Visual Media at SD Negeri 11 Trienggadeng - Nurmala; Rahmayani (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to analyze the effectiveness of using audio-visual media to improve learning outcomes of Islamic Religious Education in grade VI students of SDN 11 Trienggadeng. This study was conducted as a classroom action research consisting of two cycles, involving 30 students as research participants. The main objective of this study was to determine whether the integration of audio-visual learning materials would improve students' understanding of the topic "When the Earth Stops Spinning". The results showed a significant increase in student engagement and understanding, as indicated by an increase in the average test score from pre-test to post-test. The use of multimedia resources provides a more interactive learning experience, so that abstract concepts become more real. These findings indicate that the integration of audio-visual media in religious education can effectively improve student participation and learning outcomes.